2013
DOI: 10.1097/ede.0b013e318281a30f
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality of Workers Exposed to Styrene in the U.S. Reinforced Plastics and Composite Industry

Abstract: We found no coherent evidence that styrene exposure increases risk from cancers of the lymphatic and hematopoietic tissue, pancreas, or lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 31 publications
1
73
2
Order By: Relevance
“…The recently updated British styrene cohort also had an excess of lung cancer deaths, especially among workers with high-styrene exposure, and, like us, no leukaemia or lymphoma excess 27. However, a recent update of a large (N=15 826) US study of workers in the reinforced plastics industry originally studied by Wong and colleagues32 33 found an increase in lung cancer mortality, but with an inverse trend with exposure,26 and a previous update had found an increase in mortality from ‘other respiratory diseases’, but only in short-term (<1 year) or low-exposure workers 33. The difference in findings between our cohorts and others could be due to differences in styrene levels or lifestyle or other differences between the cohorts.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The recently updated British styrene cohort also had an excess of lung cancer deaths, especially among workers with high-styrene exposure, and, like us, no leukaemia or lymphoma excess 27. However, a recent update of a large (N=15 826) US study of workers in the reinforced plastics industry originally studied by Wong and colleagues32 33 found an increase in lung cancer mortality, but with an inverse trend with exposure,26 and a previous update had found an increase in mortality from ‘other respiratory diseases’, but only in short-term (<1 year) or low-exposure workers 33. The difference in findings between our cohorts and others could be due to differences in styrene levels or lifestyle or other differences between the cohorts.…”
Section: Discussionmentioning
confidence: 49%
“…Previous reviews and studies of lymphatic and haematopoietic neoplasm in styrene-exposed workers4 22 have varied widely, including a statistically significant deficit of cancer deaths,26 a lack of association with styrene,27 and a moderate association of increased lymphoma and leukaemia mortality with longer latency and higher average level of exposure 28. Incidence studies are preferred over mortality studies for cancers with relatively high survival rates, such as lymphohaematopoietic cancers 29 30.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large epidemiologic study described excess mortality from obstructive lung disease in highly exposed, short-term reinforced-plastics workers, which would be consistent with obliterative bronchiolitis [Collins et al, 2013; Cummings et al, 2014]. Furthermore, an occupational study in an Egyptian reinforced plastics factory found that styrene exposure correlated with decreased pulmonary function tests, including FEV1/FVC and percent of predicted FEV1, FVC, and MMEF, indicating that obstruction, especially mid-flow obstruction, might be a consequence of styrene exposure [Helal and Elshafy, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Styrene exposures are common in the reinforced plastics and composite industry, in which Collins, Bodner, and Bus () examined mortality rates in relation to cumulative exposure, duration of exposure, peak exposures, and average exposure. The peak exposure metric reflected days with 15 or more minutes above 100 ppm styrene (reportedly the lowest level at which irritation from styrene occurs).…”
Section: Case Studiesmentioning
confidence: 99%